Biochemical and morphological alterations in lungs induced by experimental inhibition of fibrinolytic activity - (:unkn) unknown (My University, 2002)
The fibrinolytic system is known to play an important role in the protection of lung architecture and function. This study investigated the effects on lungs of inhibiting the fibrinolytic system using tranexamic acid (TXA). Thirty cats were used, 15 experimental and 15 control. TXA was administered intravenously to the experimental animals for 3 h at 200 mg/kg (acute) and 7 days at 100 mg/kg (chronic). Blood samples were obtained from the carotid artery. The acute dose cats were sacrificed at 3 h and 24 h and the chronic dose cats at 8 days. Samples of inflated and fixed lung were examined morphologically and their collagen contents were determined. Fibrinolytic activity in blood samples was determined by fibrinogen degradation products levels, fibrin plate lytic area diameter, and the euglobulin lysis time. Hyperemia, lung interstitial oedema, haemorrhaging, inflammatory cell infiltration, pneumocyte type II cell proliferation, thrombosis and emphysema-related changes, characterized by enlargement of air spaces accompanied by destruction of alveolar walls, were observed in experimental cats group. None of these alterations except hyperemia and lung interstitial oedema were observed in two control animals. Electron microscopy results revealed oedema fluid in the interstitium, proliferation of pneumocyte type II cells, thickening of the alveolar septa and presence of marked amounts of collagen. Vacuoles were seen in the capillary endothelial cells. Elastic tissue was observed as elastic masses and partly disrupted, although elastic fibers were not prominent in all parts of the interstitium. Collagen content in the chronic dose experimental group was significantly higher than in all control and acute dose experimental groups. The inhibition of fibrinolytic system appears to have caused the emphysematous alterations, alveolar wall destruction and collagen accumulation possibly by causing microthromboses leading to mechanical blockage-ischemic changes, or by causing secondary fibrinolysis as a result of fibrin degradation products affecting local plasminogen activators and proteases. An injury-repair process also appears to have occurred.
Keywords: Collagen; Fibrinolytic system; Lung; Tranexamic acid